Implementasi Program Sekolah Sehat - Nursela Musalam; Ansar; Nina Lamatenggo (Transbahasa, 2026)
This study aims to describe the implementation of the Healthy School Program at SMP Negeri 4 Gorontalo, focusing on program types, stakeholder involvement, and implementation strategies. This study used a qualitative descriptive approach. Informants consisted of the principal, vice principal, teachers, and students involved in school health activities. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing. Data validity was strengthened through source and technique triangulation. The findings show that the program was implemented through five focuses: nutrition health, physical health, immunization health, mental health, and environmental health. Implementation involved the principal as policy coordinator, teachers as facilitators, students as active participants, and parents as supporters of healthy habits at home. The program was carried out through planning, routine activities, collaboration with health services, and continuous monitoring. The study concludes that the program supports a cleaner, safer, and healthier learning environment, although documentation, success indicators, and stakeholder collaboration still need strengthening.